RELATION OF CERTAIN ENDOCRINE DISTURBANCES TO SUSCEPTIBILITY OF GOLDEN SYRIAN HAMSTER TO EXPERIMENTAL POLIOMYELITIS - Teodoru, Constantin V. (The Rockefeller University Press, 1954)
Alterations in susceptibility of the Syrian hamster to poliomyelitis virus (MEF1) inoculated intracerebrally appeared closely related to seasonal changes and experimental disturbances in the adreno-testes equilibrium. Enhanced susceptibility coincided with seasonal enlargement of adrenals, followed cortisone and DOCA treatment and appeared during the initial postorchiectomy period. Increased resistance occurred incidentally to adrenalectomy, seasonal diminution in adrenal weight, testosterone overdosage, and testicular hypertrophy induced by treatment with GTH or chorionic gonadotrophin. The effect of certain hormonal interactions, the interference of conditioning factors and the role of compensatory reactions are discussed.